PERFORMING BRITISH VIOLENCE IN THE NIGERIAN MIDWEST: ABMED YERIMA’S THE TRIALS OF OBA OVONRAMWEN AND THE “NARRATIVES” OF HISTORY - Affiong Effiom (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
Theatre and its appurtenances can project events, problems and issues of society. Its hegemony consists in performances and varied possibilities of expression with great propensity to awaken social consciousness stimulate emotions, and provide certain 'experiences' to invent a 'new' future. This paper takes a look at one of such experiences through a critical appraisal of the stage performance of Ahmed Yerima's Trials of Oba Ovonramwen as presented at the Chinua Achebe Arts Theatre, University of Calabar. Invoking Elizabeth Wessling’s Writing History as a Prophet, this paper argues that the political perspective of the narrator or writer conditions the many versions of history. The politics and poetics of performance as established by Augusto Boal in many of his works suggest that history need not be written by the oppressor alone but can be subject to the re-writing and re-interpretation of the “vanquished”. In the case of Ahmed Yerima’s Trials of Oba Ovonramwen, the interpretation of history is both a creative and critical process in which the act of narration itself becomes a “symbolic” one through which past misrepresentations can be subject to critiques and re-readings. In addition to revisiting the version of this episode of “British Punitive Expedition” to the Benin Kingdom in 1897, this paper submits that through performance the oppressed can not only recuperate his/her history but also re-inscribe the correct(ed) version into the annals of global politics and archival repository.